2013
DOI: 10.1002/jgrc.20224
|View full text |Cite
|
Sign up to set email alerts
|

Examining the global record of interannual variability in stratification and marine productivity in the low‐latitude and mid‐latitude ocean

Abstract: [1] Strengthened stratification of the upper ocean, associated with anthropogenic or climatedriven warming, is generally expected to inhibit marine primary productivity in lightreplete, nutrient-limited environments, essentially, in the low and middle latitude ocean, based on the supposition that increased water column stability will inhibit vertical mixing and consequently the upward entrainment of deep nutrients into the euphotic zone. Herein, we examine the local stratification control of productivity on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
1
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 43 publications
(59 reference statements)
9
99
1
5
Order By: Relevance
“…Behrenfeld et al [38] showed that for the permanently stratified ocean (between 40°S and 40°N) there was a significant correlation between primary production and MEI. Dave and Loizier [39] attributed this correlation between primary production and MEI across all of the permanently stratified oceans to be dominated by the correlation in the Equatorial Pacific. Regionally, there was a significant correlation between the MEI and the primary production from the NOBM for 2 phytoplankton groups or more in 7 out of the 12 regions (Table 2).…”
Section: Interannual Variabilitymentioning
confidence: 98%
“…Behrenfeld et al [38] showed that for the permanently stratified ocean (between 40°S and 40°N) there was a significant correlation between primary production and MEI. Dave and Loizier [39] attributed this correlation between primary production and MEI across all of the permanently stratified oceans to be dominated by the correlation in the Equatorial Pacific. Regionally, there was a significant correlation between the MEI and the primary production from the NOBM for 2 phytoplankton groups or more in 7 out of the 12 regions (Table 2).…”
Section: Interannual Variabilitymentioning
confidence: 98%
“…Conteras et al, 2010), we compared the indices with the temperature differential between sea surface and subsurface at 200 m depth (T0 -T200, suggested as a measure for stratification by Dave and Lozier, 2013) and mean annual depths of the surface mixed layers. A significant correlation is only observed between Diol Index 1 and T0 -T200, but again this may also be 330 due to the strong correlation between SST and To -T200.…”
Section: The Values Of Diol Index 2 Showed a Geographical Distributiomentioning
confidence: 99%
“…This is likely to have significant impacts on atmospheric circulation, precipitation patterns and rates, ocean stratification, mixed-layer depth, vertical mixing, deep-water circulation, surface mixing, and horizontal and vertical advection (Dave and Lozier, 2013). In the Australian region a warming of about +0.5 °C has occurred since 1880 (HadiSST; Rayner et al, 2003) but the changes have not been homogenous.…”
Section: Introductionmentioning
confidence: 99%